From selling on e-commerce platform to selling on WeChat platform : an exploration of B2C e-commerce of agricultural byproducts in China - Wang, Kanliang, (SAGE business cases, 2015)
Although agricultural byproducts sales are dominated by traditional sales channels nowadays, recently agricultural byproducts e-commerce is developing rapidly. What to sell and how to sell on the Internet are the two most concerning problems for companies selling agricultural byproducts. To be a copycat of other business models is certainly doomed to failure. This case describes the agricultural byproducts e-commerce practice of Gongtianxia Technology Company with the aim of exploring the direction of agricultural byproducts e-commerce and sharing the lessons learned with e-commerce entrepreneurs.